Analisis Laba, Arus Kas Operasi, Leverage Dan Ukuran Perusahaan Terhadap Return Saham (Studi Kasus pada Perusahaan Dagang yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2022) - Maulida, Maulida; Fikri, M. Ali; Isnawati, Isnawati (Fakultas Ekonomi dan Bisnis Unram, 2024)
This study examines the effect of accounting profit, operating cash flow, leverage (debt to equity ratio) and company size on stock returns in trading companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. The purpose of this study was to determine the effect of the four independent variables above (accounting profit, operating cash flow, leverage and company size) on the dependent variable (stock return). This research uses quantitative methods. The sample in this study amounted to 57 trading companies. The sampling technique used in this study was purposive sampling. The results of this study indicate that accounting profit, operating cash flow, leverage (debt to equty ratio) and company size have no effect on stock returns.